Optimal control of voltage and power in a Multi Zonal Shipboard MVDC Power System - Kankanala, Padmavathy; Srivastava, Suresh C; Srivastava, Anurag K; Schulz, Noel N (2009 North American Power Symposium, 2009)
Recent advancements in Voltage Source Converters (VSCs) of high-voltage and high-power rating had a significant impact on the development of Multi-Terminal HVDC (MTDC) power transmission systems. The U.S. Navy has proposed MultiZonal Medium Voltage DC (MVDC) Shipboard Power System (SPS) architecture for the next generation of their surface combatants. A Multi-Zonal MVDC SPS consists of several VSCs exchanging power through a DC network. Following a system fault or damage, the current flow pattern in the DC distribution grid will change and the DC voltages across the VSCs will assume new values. DC voltage reference or power reference settings of VSCs have to be determined, in advance, which can maintain the voltage within desired margins (usually 5% around the nominal DC voltage) in steady state under the pre-fault as well as the post-fault conditions. This paper presents a voltage sensitivity based method and an optimization based method to determine the reference voltage and power settings of the VSCs. The results have been demonstrated on MVDC shipboard power system architecture.